Metabolic capability of Acinetobacter baumannii based on phenotype microarray analysis and the effects of selected substrates on its biofilm forming ability / Ahlam Hodaed Alsheikh - Ahlam Hodaed , Alsheikh (2018)
Acinetobacter baumannii (A. baumannii) is one of the commonly reported nosocomial infectious agents causing high morbidity and mortality worldwide. The objective of the study was to determine the metabolic capability of A. baumannii by using the Phenotype Microarray technology and to determine the effects of selected substrates on the biofilm forming ability of A. baumannii. Two strains of A. baumannii, ACIBA-46 and ACIBA- 47 which were previously isolated from the ventilator and hands of healthcare workers (HCWs), respectively, were tested. Kinetic data of utilization of various carbon, nitrogen, phosphorus and sulfur substrates which were previously generated, were converted into spreadsheet format using Biolog OmniLog Phenotype Microarray Software for further statistical analysis. The effects of selected substrates on the biofilm forming ability of these two strains were evaluated according to established protocols. The analyses of the carbon utilization data indicated that both ACIBA-46 and ACIBA-47 strains had a low carbon catabolic capability, utilizing only 48 of 190 (25%) carbon substrates tested. However, the HCWs strain A. baumannii ACIBA-47 appeared to utilize a higher number of carbon substrates (6 carbons) compared to the ventilator strain ACIBA-46. Both of the A. baumannii strains mainly used the two classes of carboxylic acids and amino acids as carbon sources, which include alanine, asparagine, serine, histidine, ornithine, arginine, pyruvic acid and succinic acid that are associated with energy metabolism. Interestingly, this study found some of nitrogen substrates inhibited the growth of ACIBA-46 strain such as uric acid and alloxan. Both ACIBA-46 and ACIBA-47 strains were able to form a moderate biofilm in rich medium (LB broth), but were non-biofilm formers in nutrient depleted medium (M9MM). When M9MM was supplemented with 22 substrates (tested individually), there was a change in the biofilm forming ability for both strains. Substrates such as, L- arabinose, L- arginine and urea slightly increased the ability of forming biofilm for both strains. In addition, substrates such as L-histidine, L- leucine and thymidine were moderately increased the ability to form biofilm for both strains. However, substrates such as glycine and Tween 80 showed no effect on the biofilm forming ability of A. baumannii ACIBA-46 and ACIBA-47 strains. The elucidation of the metabolic activity of A. baumannii will offer scientists insight into ways to manipulate such activity either to curtail the pathogens success or enhance its susceptibility to antibiotic agents.